Juez inteligente. Expert system that assists the judge in the assessment of judicial proof - Vargas Vélez, Orión (2021)
Juez Inteligente is an expert system that –based on the credentials of evidence (credibility, relevance and inferential force or weight), rules of experience and rules of science– assists the student, professor, attorney at law, prosecutor or judge, in the construction of evidential structures, arguments or inferences, which make it possible to determine the claim or hypothesis that is more or less probable in a judicial trial. In this paper, some approximations about the Intelligent Judge expert system are presented, with the intention that it can be implemented in the future in different latitudes.